1961
DOI: 10.1037/h0093808
|View full text |Cite
|
Sign up to set email alerts
|

An experimental analysis of associative factors in mediated generalization.

Abstract: For more than two thousand years men have concerned themselves with the question of how ideas become associated or connected to one another. The concern here is primarily with the importance of the temporal order of associating independent elements with the common element and the direction of association between the independent elements and the common element in the verbal transfer situation. Several theories have been proposed which deal with the nature of mediated generalization, and though they differ somew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

1963
1963
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(42 citation statements)
references
References 29 publications
2
40
0
Order By: Relevance
“…The results indicated a significant reverse mediation effect, which clearly supports the findings of several investigators (e.g., Horton & Kjeldergaard, 1961;McCormack, 1961;and Jenkins, 1963). Essentially the C-A pairs, which have in common an association with a B-word, were learned faster during the test stage than the C-A pairs with no such connection.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The results indicated a significant reverse mediation effect, which clearly supports the findings of several investigators (e.g., Horton & Kjeldergaard, 1961;McCormack, 1961;and Jenkins, 1963). Essentially the C-A pairs, which have in common an association with a B-word, were learned faster during the test stage than the C-A pairs with no such connection.…”
Section: Discussionsupporting
confidence: 80%
“…Twenty-four low-frequency five-letter words selected from the Thorndike-Lorge list (1944) and scaled for association values by Horton & Kjeldergaard (1961) were assigned to four separate lists as shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…A number of studies have demonstrated the facilitating and interfering effects of implicit verbal mediators on the paired-associate learning of adults (e. g., Horton & Kjeldergaard, 1961;McGehee & Schulz, 1961). The results of the present study indicate that some of the same phenomena occur in the verbal paired-associate learning of children.…”
supporting
confidence: 65%
“…This alternative interpretation is diametrically opposed to an argument based on associative mediation which states that the pre sen c e of the B association in Stage III facilitates acquisition. The general reasoning applies similarly to the other mediation paradigms discussed by Horton & Kjeldergaard (1961) and Jenkins (1963).…”
Section: Dilwusslonmentioning
confidence: 96%